PENGUKURAN DAN PERBAIKAN TOTAL PRODUCTIVE MAINTENANCE (TPM) MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN ROOT CAUSE FAILURE ANALYSIS (RCFA) - Amrussalam, Amrussalam; Santoso, Purnomo Budi; Tama, Ishardita Pambudi (JEMIS (Journal of Engineering & Management in Industrial System), 2016)
Total productive Maintenance (TPM) is an initiative to optimize the effectiveness  of manufacturing equipment which the objectives are elimination of all accidents, defects and downtimes [5].  The fundamental measurement of   TPM    using  a method   called the Overall Equipment Effectiveness (OEE). The study  was began by  root cause   identification of losses using  Root Cause Failure anaysis (RCFA), OEE was calculated based on the metrics  calculation which consist of availability metrics, performance metrics, and quality metrics, while reliability was calculated based on the value of MTBF.It is followed by recommendation of TPM  for  improvement of  losses .  The results  of this study  indicate that the value of OEE is not  achieve of world-class standards, where OEE is only  35,38%. The  factor witch greatly affects of   poor  OEE and reliability is  downtime loss  in the machine, which   is 2394,8 sec / process / day or 88,07% of all total losses. The proposed  improvements of losses  are application  of Autonomous Maintenance and  5S concept, making of  the preciseprocess operating standard   based on  the machine conditions,  need for planned maintenance, focused improvement,  quality maintenance and most important, supervision of the machine operator.